Eye-Hand Coordination, Wrist Flexibility, and Long-Serve Performance in Beginner Badminton Players: A Cross-Sectional Correlational Study - Rodi Al-Ashfihani; Didik Daniyantara; Gani Prasetyo (Darul Yasin Al Sys, 2026)
Long-serve performance in badminton depends on directional accuracy, timing, and efficient coordination of the upper-limb kinetic chain; however, evidence-based assessment of service skills among beginner players remains limited. This study aimed to examine the associations between eye-hand coordination, wrist flexibility, and long-serve performance among players at SMKN 1 Sikur. A cross-sectional correlational design was applied involving 20 players. Eye-hand coordination was assessed using a tennis-ball throw-and-catch test, wrist flexibility was measured with a goniometer, and long-serve performance was evaluated using a standardized long-service test. Data were analyzed using Pearson correlation coefficients, coefficients of determination, and 95% confidence intervals to estimate the magnitude and precision of the associations. The findings showed that eye-hand coordination was not significantly associated with long-serve performance (r = -0.318, p = 0.171, 95% CI [-0.667, 0.144], R² = 0.101), whereas wrist flexibility demonstrated a moderate positive association with long-serve performance (r = 0.487, p = 0.030, 95% CI [0.056, 0.765], R² = 0.237). These results indicate that wrist flexibility may serve as a useful and low-cost screening and training target for developing long-serve performance among beginner badminton players. Conversely, generic eye-hand coordination tests should be complemented by badminton-specific perceptual-motor and technical assessments. The study contributes to service-skill assessment literature by identifying a practical physical factor associated with beginner long-serve performance, although the small sample size and cross-sectional design limit causal inference and highlight the need for replication using larger samples, reliability testing, and motion-analysis measures.